Effect of soil environment on the photo‐degradation of polyethylene films. Issue 39 (3rd July 2015) - Gauthier, Emilie; Nikolić, Melissa; Truss, Rowan; Laycock, Bronwyn; Halley, Peter
ABSTRACT Outdoor weathering field trials performed with oxo‐degradable polyethylene (PE) thin films were conducted across temperate, grassland, and subtropical sites around Australia. It was found that a site factor, that was apparently independent of total solar dose and temperature, significantly impacted the rate and extent of photo‐oxidation. Controlled laboratory‐based accelerated aging trials of both PE film with no prodegradant and oxo‐degradable PE films (containing iron stearate) revealed that the rate and extent of PE photo‐oxidation did not correlate with temperature under the film or UV exposure, but was soil dependent. Under accelerated photo‐oxidative conditions, the time to reach embrittlement for a PE film aged over the soil from the temperate site (OM 8.4) was half (24.5 days) the time taken when aged over air (48 days). Further investigation revealed that humic acids and fulvic acids within soil organic matter may contribute to an increased rate of PE photo‐oxidation, possibly through the formation of volatile reactive oxygen species that may form under photo‐oxidative conditions. The presence of water also had a significant impact on the rate of photo‐oxidation. Overall, the impact of soil on PE photo‐oxidation was found to be complex and likely dependent at least in part on soil components that varied between different soil types, consequently influencing their photo‐chemistry. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42558.